1994
DOI: 10.1070/rc1994v063n04abeh000090
|View full text |Cite
|
Sign up to set email alerts
|

The properties and applications of fluorine-containing polymer films with piezo- and pyro-activity

Abstract: Polymer films based on poly(vinylidene fluoride) and its copolymers, which exhibit piezo-and pyro-electric properties after appropriate treatment, are described. The principal advantages of materials of this class include high values of the piezomoduli, which permit their practical use. Another valuable property, which is difficult to achieve in inorganic materials, is the wide range of frequencies over which the given active element can operate. The possibility of achieving large areas and fairly simple metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 68 publications
0
33
0
Order By: Relevance
“…Ferroelectricity 1,2 and high piezo-and pyroactivity in these compounds, along with specific properties of polymers, allow to use them as a material for various energy converters. 3,4 Mechanisms of ferroelectricity and piezoelectricity are still not clearly understood, 2,5,6 particularly the role of molecular mobility in crystalline and especially in the amorphous phase is not clear in these phenomena. Therefore, investigation of mechanisms of molecular dynamics in considered class of polymers is actual.…”
Section: Introductionmentioning
confidence: 98%
“…Ferroelectricity 1,2 and high piezo-and pyroactivity in these compounds, along with specific properties of polymers, allow to use them as a material for various energy converters. 3,4 Mechanisms of ferroelectricity and piezoelectricity are still not clearly understood, 2,5,6 particularly the role of molecular mobility in crystalline and especially in the amorphous phase is not clear in these phenomena. Therefore, investigation of mechanisms of molecular dynamics in considered class of polymers is actual.…”
Section: Introductionmentioning
confidence: 98%
“…1 ' 2 It is one of the most promising polymeric ferroelectrics. It is used for practical purposes in the polarised state (for example, in various kinds of transducers 3 ), so that knowledge of the mechanism of the structural changes in strong electric fields is obligatory. Analysis of published studies has shown that polarisation processes depend on the characteristics of the structure and the nature of the molecular mobility in crystalline and amorphous regions.…”
Section: Introductionmentioning
confidence: 99%
“…For most applications, PVDF films with enhanced ferroelectric properties are required since it has been established that coefficients of both piezo-and pyroactivity increase linearly with remnant polarization. [7] For homopolymer PVDF, polarization is highest in the b-crystalline form but experimentally realized ferroelectric properties are much below theoretical predictions. Ferroelectric polarization of PVDF could be significantly improved by forming a copolymer with 20-40 mol-% trifluoroethylene (TrFE).…”
Section: Introductionmentioning
confidence: 90%
“…[1] Among the few such polymers, poly(vinylidene fluoride)(PVDF) is widely studied and several device applications in nonvolatile solidstate memories, [2] thermal imaging, [3] sensors, [4] transducers, [5] radiation detectors, [6] energy conversion, [1,7] etc., have emerged. For most applications, PVDF films with enhanced ferroelectric properties are required since it has been established that coefficients of both piezo-and pyroactivity increase linearly with remnant polarization.…”
Section: Introductionmentioning
confidence: 99%